REALISASI PEMBERIAN UPAH TERHADAP PETUGAS ILI-ILI DESA TANJUNGSARI DALAM PERSPEKTIF HUKUM SYARIAH - Muhajir Muhajir (Jurnal Ilmiah Ekonomi Islam, 2021)
Farmer are one of the livelihoods of residents in the village of Tanjungsari, Kutowinangun sub-district, kebumen district to make ends meet. To irrigate their agricultural land, apart from relying on rainfall, they also rely on irrigation water supplied by ili-ili officers. Ili-ili officers get wages from farmers with the provision of 10 kg of unhullud rice for 100 rice fields, the payment is deferred after the harvest arrives. But in reality the farmers do not pay according to the provisions. This resulted in ili-ili officers experiencing losses. Based on the description above, the problem can be formulatedhow the practice of giving wages to ili-ili officials in a legal perspective. In this study using the type of field research, in data collection by means of direct interviews with farmers and ili-ili officers. The nature of this research is a descriptive analysis approach. From the research that has been done, it can be concluded that the wages of ili-ili officers are in accordance with the provisions of Islamic law, which includes the wages ajrul miṡli.